ANALISIS PENDAPATAN DAN KELAYAKAN USAHA TANI JAGUNG DI DESA POOPO KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - Riko Rudolf Ratu; Paulus A. Pangemanan; Theodora M. Katiandagho (Sam Ratulangi University, 2021)
This study aims to determine determine the amount of corn farming income and whether corn farming is feasible to be cultivated by corn farmers in Poopo Village, Modoinding District, South Minahasa Regency. This research was conducted from December 2019 to February 2020. The data used are primary data obtained through interviews with 30 (thirty) respondents of scallion farmers. The method used in this research uses descriptive quantitative and is presented in tabular form. The data analyzed included: income analysis and contribution analysis. The results showed that The average income of corn farmers in Poopo Village, East Passi Subdistrict, is Rp 2.786,363,89 / farmer and Rp 2.604,078,40 / ha, with an R / C value generated per farmer of 1.06. The value of R / C ratio produced is more than one, indicating that maize farming in Poopo Village, Passi Timur District, Bolaang Mongondow Regency is profitable and feasible to operate.